Innovative mobile and Internet services in ubiquitous computing : proceedings of the 13th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2019) /: proceedings of the 13th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2019). (2020) - Unknown
No abstract available